(untitled) (Bangladesh Journal of Zoology, 2015)
A study was done on nesting colonies of Little Cormorant (Phalacrocorax niger) in different study areas of Bangladesh from 2003 to 2005. The study sites were Eidgah in Coxs Bazar, Bhuyapur in Tangail, Bhairab and Tarail Upazilla in Kishorganj, Dimla in Nilfamari, Singair Upazilla in Manikganj and Matlab in Chandpur district. These sites were visited at regular interval to know about the characteristics of different nesting colonies and causes of their decline and threats for the Little Cormorant. The village markets and school areas were visited to know about the location of nests, different threats against them and information about the present situation of Little Cormorant and also for creation of awareness for their conservation. The nesting habitats of the Little Cormorant were situated in the homestead areas in all the cases. The highly preferred sites for nesting were near a pond (75%). Bamboo (Bambusa arundinacea) was the highly preferred nesting trees (25%). The nesting height varied from 8.84 m to 10.66 m. Association of the Little Cormorant in the colony was found with Ardeaola grayii (30%), Egretta garzetta (30%), Mesophoyx intermedia (30%), Casmerodius albus (5%) and Pteropus giganteus (5%). The nesting colonies of the Little Cormorant were destroyed by human (92.9%) and river erosion (7.1%). It was observed that awareness campaign will help for the conservation of the bird. Bangladesh J. Zool. 42(1): 35-44, 2014